Case Report: A Patient With Neuroleptic Malignant Syndrome, Water Intoxication and Hyponatremia Associated With Severe Cerebral Edema and Coma - Takenouchi, Haruka; Anno, Takatoshi; Kimura, Yukiko; Kawasaki, Fumiko; Shirai, Ryo; Kaneto, Hideaki; Kurokawa, Katsumi; Tomoda, Koichi (Frontiers in Endocrinology, 2022)
Background: Water intoxication is typically caused by primary or psychogenic polydipsia that potentially may lead to fatal disturbance in brain functions. Neuroleptic malignant syndrome (NMS) is a serious complication induced by administration of antipsychotics and other psychotropic drugs. The combination of inappropriate secretion of antidiuretic hormone (SIDAH), NMS and rhabdomyolysis have been rarely reported. Our patient also developed severe water intoxication. Case presentation: Herein we report a comatose case of NMS complicated with water intoxication, syndrome of SIADH and rhabdomyolysis. This patient had severe cerebral edema and hyponatremia that were improved rapidly by the correction of hyponatremia within a couple of days. Conclusions: Malignant neuroleptic syndrome water intoxication, SIADH and rhabdomyolysis can occur simultaneously. Comatose conditions induced by cerebral edema and hyponatremia can be successfully treated by meticulous fluid management and the correction of hyponatremia.